Can emotional accessibility mitigate the risk of sexual challenges to relationship happiness among older adult couples? - Hodges, Sally Jane (Kansas State University, 2018)
Much of the literature in sexuality and aging focuses on the physical aspects of the sexual relationship such as dysfunction and decline in frequency. In doing so, aging is viewed in a negative light because of its implied connection to dull sexuality and poor sexual satisfaction. However, despite potential age related sexual changes, many couples remain happy later in life in their relationships. Using data from 3,005 adults over the age of 57 from the National Social Life, Health and Aging Project data, we tested hypotheses using three different age groups: Newly Old (57-64), Young-Old (65-74), and Old (75-85). The results indicated that across each age group physical pleasure was linked with relationship happiness and emotional satisfaction. However, sexual frequency was not linked with relationship happiness or emotional satisfaction. In several cases, emotional accessibility moderated—served as a protective factor—in the associations between the nature of the sexual relationship and the nature of the quality of the romantic relationship. Clinical implications include identifying a clinically modifiable factor—emotional accessibility—that may mitigate the potential risk of changing sexuality to overall relationship happiness within older adult couples.
Keywords: Older adults; Emotional accessibility; Sex frequency; Sexual challenges; Relationship satisfaction; Sex satisfaction